TEORI-TEORI KEPEMIMPINAN - Sulthon Syahril (Pascasarjana IAIN Metro, 2019)
Leadership is a classic topic of discussion, but it is still very interesting to be researched because it is very decisive for an organization. Leadership is essentially the responsibility. Strong leadership is needed so that the organization can achieve its goals. Leadership is a process of influencing others to do their work according to the expected goals. Leadership has a broader understanding of power because leadership is an effort to influence people not just to do what the boss wants but also to achieve the goals of the organization's goals. This study aims to determine how the notion of leadership and leadership in Islam and how leadership theories. These results show leadership a process of how to organize and achieve performance to achieve: Leadership decisions in the Islamic view of trust that must be carried out in accordance with the objectives well and accountable not only in the world but also before God later in the hereafter